A novel homolateral and dicationic AIEgen for the sensitive detection of casein. Issue 11 (10th May 2019) - Li, Zenghe; Wang, Lianying; Guan, Weijiang; Ding, Caifeng; Yuan, Zhiqin; Lu, Chao
Abstract : Sensitive casein detection using a homolateral and dicationic AIEgen is presented. Abstract : The exploitation of highly soluble and responsive AIEgens is essential for further expansion of their practical applications. In this study, dipropyltrimethylammonium bromide-substituted TPE (denoted as o -TPEDTA), a homolateral and dicationic AIEgen, was synthesized and applied for the turn-on detection of casein via hydrophobic interactions. The rapid and sensitive detection of casein was achieved using the designed o -TPEDTA probe with the limit of detection of 0.05 μg mL −1 . The satisfying selectivity of over 1000-fold concentration of other probably existing chemicals, including amino acids, sugars and salts, was achieved due to the strong binding affinity between o -TPEDTA and casein. The evaluation of casein in milk powder samples with small relative standard deviations was realized using the o -TPEDTA probe. The accuracy of the o -TPEDTA probe-based detection method was validated by the consistency of the casein detection results with those obtained via a national standard casein evaluation approach.